ASSVd infection inhibits the vegetative growth of apple trees by affecting leaf metabolism - Li, Guofang; Li, Jinghong; Zhang, He; Li, Jiuyang; Jia, Linguang; Zhou, Shiwei; Wang, Yanan; Sun, Jianshe; Tan, Ming; Shao, Jianzhu (Frontiers in Plant Science, 2023)
Apple scar skin viroid (ASSVd) can infect apple trees and cause scar skin symptoms. However, the associated physiological mechanisms are unclear in young saplings. In this study, ASSVd-infected and control ‘Odysso’ and ‘Tonami’ apple saplings were examined to clarify the effects of ASSVd on apple tree growth and physiological characteristics as well as the leaf metabolome. The results indicated that leaf ASSVd contents increased significantly after grafting and remained high in the second year. Leaf size, tree height, stem diameter, branch length, and leaf photosynthetic efficiency decreased significantly in viroid-infected saplings. In response to the ASSVd infection, the chlorophyll a and b contents decreased significantly in ‘Odysso’, but were unchanged in ‘Tonami’. Moreover, the N, P, K, Fe, Mn, and Ca contents decreased significantly in the leaves of viroid-infected ‘Odysso’ or ‘Tonami’. Similarly, the CAT and POD contents decreased significantly in the viroid-infected saplings, but the SOD content increased in the viroid-infected ‘Tonami’ saplings. A total of 15 and 40 differentially abundant metabolites were respectively identified in the metabolome analyses of ‘Odysso’ and ‘Tonami’ leaves. Specifically, in the viroid-infected ‘Odysso’ and ‘Tonami’ samples, the L-2-aminobutyric acid, 6ʺ-O-malonyldaidzin, and D-xylose contents increased, while the coumarin content decreased. These metabolites are related to the biosynthesis of isoflavonoids and phenylpropanoids as well as the metabolism of carbohydrates and amino acids. These results imply that ASSVd affects apple sapling growth by affecting physiological characteristics and metabolism of apple leaves. The study data may be useful for future investigations on the physiological mechanisms underlying apple tree responses to ASSVd.